Cytotoxic effect of betulinic acid and betulinic acid acetate isolated from Melaleuca cajuput on human myeloid leukemia (HL-60) cell line - Faujan, Nur Hana; Mohammed Alitheen, Noorjahan Banu; Yeap, Swee Keong; Ali, Abdul Manaf; Hamid, Muhajir; Ahmad, Faujan (Academic Journals, 2010)
The cytotoxic effect of betulinic acid (BA), isolated from Melaleuca cajuput a Malaysian plant and its four synthetic derivatives were tested for their cytotoxicity in various cell line or peripheral blood mononuclear cells (PBMC) by 3-[4,5-dimethylthizol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. Betulinic acid acetate (BAAC) was most effective than other betulinic acid derivatives. It had most active cytotoxic activity against human myeloid leukemia (HL-60), human T4-lymphoblastoid (CEM-SS), BALB/c murine myelomonocytic leukemia (WEHI-3B) and human cervical epithelial carcinoma (HeLa) but not on normal human lymphocytes (PBMC), suggesting its action is specific for tumor cells. BA and BAAC inhibit HL-60 cell line at low concentration after 72 h with IC50 values at 2.60 and 1.38 g/mL, respectively. DNA fragmentation analysis showed ladder formation in the 100 - 1500 bp region in HL-60 cell lines after 24 h of treatment with IC50 values. The induction of apoptosis was also confirmed by flow cytometric analysis of cell cycle. BA and BAAC have been shown to induce a time dependant increase in the sub G1 peak indicating apoptotic phenomenon as obtained from the DNA content histogram analysis. Thus, betulinic acid isolated from Malaysia plant showed good potential as an anti-cancer compound with less toxicity to human normal cells.